Odpowiedź :
a-[a-(1-a)]= a - (a - 1 + a) = a - a +1 - a = 1 - a
-x-[-(1-x)-(x-1)]= -x - (-1 + x - x +1) = -x
x-[y-(x-y)-x-(y-x)]= x - (y - x + y - x - y + x) = x - (y - x) = x - y + x = 2x - y
1-a-[1-(a-1)-2a-(1-3a)]-a-1= 1 - a - (1 - a + 1 - 2a - 1 + 3a) - a - 1 =
= -2a - 1
-x-[-(1-x)-(x-1)]= -x - (-1 + x - x +1) = -x
x-[y-(x-y)-x-(y-x)]= x - (y - x + y - x - y + x) = x - (y - x) = x - y + x = 2x - y
1-a-[1-(a-1)-2a-(1-3a)]-a-1= 1 - a - (1 - a + 1 - 2a - 1 + 3a) - a - 1 =
= -2a - 1
Podane wyrażenia zapisz w jak najprostszej postaci.
a. a-[a-(1-a)]=a-2a+1=-a+1
b. -x-[-(1-x)-(x-1)]=-x
c. x-[y-(x-y)-x-(y-x)]=x-[y+y-y-x-x+x]=x+x-y=2x-y
d.1-a-[1-(a-1)-2a-(1-3a)]-a-1= 1-a-[-a-2a+3a+1+1-1]-a-1=1-a-1-a-1=-2a-1
a. a-[a-(1-a)]=a-2a+1=-a+1
b. -x-[-(1-x)-(x-1)]=-x
c. x-[y-(x-y)-x-(y-x)]=x-[y+y-y-x-x+x]=x+x-y=2x-y
d.1-a-[1-(a-1)-2a-(1-3a)]-a-1= 1-a-[-a-2a+3a+1+1-1]-a-1=1-a-1-a-1=-2a-1